A New Approach for the Utilization of Technical Egg Albumen Based on Acid–Thermal Coagulation - Plamen Saraliev; Desislav Balev; Desislava Vlahova-Vangelova; Nikolay Kolev; Stefan Dragoev (Applied Sciences)
Technical albumen (TA) is liquid waste from egg processing enterprises and occupies a share of 10–15% of the waste. Proteins have the property at the isoelectric point of weakening their repulsive forces. This property is the basis of a TA recovery method using pretreatment to reduce moisture before drying. In this study, we present the results of a TA processing method using two types of citric and phosphoric acids based on thermal–acid coagulation as an alternative to spray drying. By analyzing physicochemical and microbiological indicators, the raw TA and the finished product are described. In this study, the characteristics of raw TA and its final product are presented. TA contains mainly water, fat, and protein, including all essential amino acids, all of the proteins of the egg white, and some of the yolk. Initially, TA is significantly microbiologically contaminated. A better yield was obtained when using citric acid 97.79% instead of phosphoric acid. The final dried egg product from TA has a protein content of 46% and a fat content of 33%. The dried egg products undergo changes in the lipid and protein fraction during storage, but the values remain low TBARS to 4 mg MDA/kg. Microbiological contamination has decreased due to a decrease in water activity to a level that meets the requirements of European legislation for the processing of animal by-products (ABPs) and uses as feed.